An evaluation of the real estate market development with a special consideration of the building process stage - Mach, Łukasz (Ocena potencjału rozwoju rynku mieszkaniowego ze szczególnym uwzględnieniem etapów procesu budowlanego, 2016)
In this article the author attempts to define, parameterize, evaluate and conduct a synthetic analysis of development potential in the area of the regional real estate market. The scope of analysis was defined according to the methodology of real estate quantification accepted by the Central Statistical Office. The Central Statistical Office in defining the process of the real estate market distinguished four research areas. These are the following: planning permissions which were issued, apartments which are under construction, apartments put into use and sales of building-assembly production executed by construction companies. The conducted research enables to evaluate the development of particular provinces in the area of the real estate market. The above mentioned evaluation, which depicts the potential of the regional residential market, is the starting point for the synthetic analysis of the obtained results. Simultaneously it enables to indicate changes in the development potential of local real estate markets
Ekonometria = Econometrics, 2016, Nr 4 (54), s. 95-107
Keywords: real estate market; development potential; building process; multivariate comparative analysis; rynek nieruchomości mieszkaniowych; potencjał rozwoju; proces budowlany; wielowymiarowa analiza porównawcza